2018
DOI: 10.1039/c7cc09266k
|View full text |Cite
|
Sign up to set email alerts
|

High quantum yield Ag2S quantum dot@polypeptide-engineered hybrid nanogels for targeted second near-infrared fluorescence/photoacoustic imaging and photothermal therapy

Abstract: A high quantum yield (4.3%) hybrid nanogel system based on engineered polypeptides and AgS quantum dots has been developed as a multifunctional diagnostic and therapeutic agent for targeted second near-infrared fluorescence, photoacoustic imaging, and photothermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…Other than polymer and metal coating, some biomolecules such as DNA, proteins and enzymes have also been demonstrated as potential matrix to enhance the colloidal stability and moderate the toxicity of inorganic nanomaterials. [11e,f,13b,28d,g,31] For instance, human serum albumin (HSA) has been applied to encapsulate Ag 2 S and rare‐earth nanoparticles to ensure their aqueous dispersibility and stability. [13b] Using tumor‐targeted fluorescence imaging as an example, the biodistribution of 100 nm HSA‐coated rare‐earth‐doped sodium yttrium fluoride (NaYF 4 ) core‐shell nanoparticles can be modulated and optimized through fine‐tune the coating thickness of the HSA shell.…”
Section: Nir‐ii Fluorescence Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Other than polymer and metal coating, some biomolecules such as DNA, proteins and enzymes have also been demonstrated as potential matrix to enhance the colloidal stability and moderate the toxicity of inorganic nanomaterials. [11e,f,13b,28d,g,31] For instance, human serum albumin (HSA) has been applied to encapsulate Ag 2 S and rare‐earth nanoparticles to ensure their aqueous dispersibility and stability. [13b] Using tumor‐targeted fluorescence imaging as an example, the biodistribution of 100 nm HSA‐coated rare‐earth‐doped sodium yttrium fluoride (NaYF 4 ) core‐shell nanoparticles can be modulated and optimized through fine‐tune the coating thickness of the HSA shell.…”
Section: Nir‐ii Fluorescence Imagingmentioning
confidence: 99%
“…From the nanomaterial design perspective, biocompatible inorganic NIR‐II emissive contrast agents have also found their usage in pharmaceutical research and development to leverage on the diagnostic function. [28f,31–32] Great efforts have been devoted to developing theranostic nanoplatforms, which can assist clinicians in real‐time visualization of therapeutic effect. Therefore, in addition to developing NIR‐II emissive inorganic nanomaterials with a simple targeting function, other therapeutic and imaging modalities have been integrated into a single nanoformulation.…”
Section: Nir‐ii Fluorescence Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels that contain both hydrophobic region and hydrophilic region will address this problem due to little effect on the microenvironment of hydrophobic QDs. We have previously reported that the QY of Ag 2 S QDs have not changed significantly by using encapsulation with PC 10 A polypeptide …”
Section: Methodsmentioning
confidence: 99%